Roof-integrated PV in Nordic Climate - Building Physical Challenges. (November 2015) - Gullbrekken, Lars; Kvande, Tore; Time, Berit
Abstract: Use of photovoltaics (PV) is key remedies in buildings where a large part of the energy supply should be based on renewable energy. PV in Nordic climate can be challenging because ofand temperatures below zero. The aim of this research work has been to provide a state-of-the art overview of recent experiences and challenges for building physical conditions related to the use of roof-integrated PV in Nordic climate. The study has identified practical guidelines for installation and ventilation of the roofing as challenges to be solved for extensive use of such systems in Nordic climate.